A new species of Ischnomesidae (Crustacea: Isopoda) from the Southern Ocean,Stylomesus weddellensis sp. nov. - Brandt, Angelika; Andres, Hans Georg (Zootaxa, 2008)
Stylomesus weddellensis sp. nov. is described from the abyssal Weddell Sea, Southern Ocean. It can easily be distinguished from the other species of the genus by its typical spine pattern. Besides the long frontolaterally directed projections of pereonite 1, pereonites 1-3 bear two mediolateral to caudolateral blunt spines which are absent in all other Southern Ocean or South Atlantic species of Stylomesus Wolff, 1956. The pereopod 7 is present, and is not fused to pleotelson. A list of all currently known 17 species of Stylomesus is presented including data on depth and distribution.